Highly transparent singlet fission solar cell with multistacked thin metal contacts for tandem applications. (21st July 2017) - Lee, Ju Min; Futscher, Moritz H.; Pazos‐Outón, Luis M.; Ehrler, Bruno
Abstract: Singlet fission solar cells combined with silicon photovoltaics allow the construction of parallel tandem solar cells, which benefit from better usage of high‐energy photons. A key limiting factor for the performance of such a tandem configuration is the transparency of the singlet fission front cell. Here we show highly transparent singlet fission solar cells with a top contact of thin Ca:Ag blends. The optimized contact leads to 81% average solar cell transmittance in the near‐infrared while maintaining more than half the short‐circuit current density compared with an opaque device. We simulate the performance of the parallel tandem stack and assess the improvements needed to fully realize the potential of singlet fission in this device configuration. Abstract : Singlet fission down conversion can be used to voltage‐match a high‐band gap solar cell with a silicon solar cell for parallel‐connected tandem solar cells. Thus far, the transparency of singlet fission cells is not high enough. Here we show that thin multistacked metals as a top contact of a novel inverted singlet fission solar cell allow for high optical transmittance, leading to >80% average solar cell transmittance in the near‐infrared, maintaining more than half of the short‐circuit current density.